Acculturation experiences among Chinese international students: A systematic review of qualitative studies - Zhao, Wei; Razak, Norsafatul Aznin A.; Nor, Azmawaty Mohamad (Journal of International Students, 2026)
Chinese international students (CIS) are among the largest and most mobile student populations globally, yet their acculturative experiences in host countries remain complex and underexplored. This systematic literature review synthesizes qualitative research on the acculturation experiences and stressors faced by CIS in foreign universities. Drawing on 16 peer-reviewed studies (2014-2024), the review explores the psychological outcomes and key stress domains: linguistic, academic, social, financial, and environmental. While some students reported personal growth and academic enrichment, the majority experienced significant challenges shaped by structural misalignments between their cultural-educational backgrounds and host country systems. These interrelated stressors often compound negative impacts on mental health and academic performance. This review addresses a gap by centering qualitative insights into how CIS navigate context-dependent transitions. By illuminating systemic and interpersonal dynamics underlying acculturative stress, the study offers a reflective lens for students, institutions, and policymakers seeking more equitable and supportive international education environments.